Studies of viral entry and viral proteases of coronaviruses and caliciviruses - Perera, Krishani Dinali Imasha (Kansas State University, 2022)
Rabbit hemorrhagic disease virus (RHDV) is a pathogenic lagovirus in the Caliciviridae family, which is associated with ongoing outbreaks in the US since 2020. Although vaccines are available, there is no specific treatment against RHDV. Lagovirus-encoded 3C-like protease (3CLpro) is a promising therapeutic target as it is critical for virus replication. In chapter 2, we identified 3CLpro inhibitors that are effective against pathogenic lagoviruses in vitro that could be developed into broad-spectrum antivirals to target multiple lagoviruses. Feline infectious peritonitis virus (FIPV) is a virulent feline coronavirus that causes a fatal systemic infection in cats. FIPV also encodes a 3CLpro, which is essential for the replication of the virus. We passaged FIPV in the presence of 3CLpro inhibitors to investigate the generation of antiviral resistance in chapter 4. Our results showed that mutant FIPV reduce the susceptibility to 3CLpro inhibitors, which can be recovered by the addition of P-gp inhibitors in cell culture. Therefore, the role of P-gp activity in the generation of resistance to 3CLpro inhibitors in FIPV needs further investigations. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of COVID-19 pandemic. In chapter 6, we studied the entry of SARS-CoV-2 in cell lines expressing angiotensin-converting enzyme 2 (ACE2) from different animal species using a pseudovirus system. We identified that all the tested animal ACE2 receptors supported the entry of pseudoviruses at various levels. Combinations of spike mutations found in variants had various effects on the entry of pseudoviruses into ACE2 expressing cells. This study contributes to the understanding of the SARS-CoV-2 host range and the effect of spike mutations on the entry of the virus into human and animal ACE2 expressing cells.
Keywords: Antiviral resistance in FIPV; P-glycoprotein; 3C-like protease inhibitors; Rabbit hemorrhagic disease virus; RNA viruses; SARS-CoV-2